Trajetórias afetivas, sexuais e reprodutivas de jovens mulheres em vulnerabilidade social: experiências de socialização - França, Giselli de Oliveira (2014)
This qualitative research aims to analyze the emotional, sexual and reproductive trajectories of young mothers who have experienced social vulnerability, including the condition of institutional shelters. The goal is to evaluate how young girls perceive the relationship between their life experiences and how they experience sexuality, maternity and affection. The concept of socialization adopts Berger and Luckmann referential, and the gender concept follows the definition of Joan Scott. The methodology of History of Life, within the field of Oral History was adopted. Five interviews with young mothers who had the experience of sheltering next to Sorocaba (SP) were conducted. Two interviews were transcribed in full and deeply examined. In the analysis, the impact of various socializing agents was discussed- public and private, and the social construction of women's identities, especially motherhood. The analysis of the life stories of these young people allows us to understand motherhood as a marker of their sedentarization, who usually have a history marked by nomadism. Moreover, the reports allowed reflections on gender relations, the social and historical construction of the role of women in our society. The absence of programmatic responses referring to this population was discussed, as well.